Systematic Changes in Gamut Size Affect Color Preference. Issue 1 (2nd January 2017) - Wei, Minchen; Houser, Kevin W.
ABSTRACT: Past work has suggested that light source color rendition can be better characterized using measures of color fidelity (for example, IES Rf, Color Quality Scale (CQS) Qf ) and relative gamut (for example, IES Rg, CQS Qg ) together, rather than using only a single measure of color fidelity. Sources with larger gamut generally enhance object chroma, which past work has found to be preferred. Few studies, however, have investigated whether excessively large gamut may lower color preference due to oversaturation. A pilot study was conducted to investigate whether an upper limit of gamut should be set to avoid oversaturation. Six nearly metameric stimuli with a correlated color temperature (CCT) near 2950 K were created using a spectrally tunable luminaire. The stimuli had a similar Qf near 50 and a range of Qg from 97 to 140. Eighteen participants between 21 and 35 years made color preference assessments of chromatic objects in a viewing booth. A forced choice protocol was employed, where participants evaluated pairs in a sequential mode. Participants preferred the appearance of object colors under stimuli having a Qg between 116 and 134 to those under the stimuli having a Qg of 97, 106, or 140, illustrating that some increase in saturation was preferred and also suggesting that oversaturation may reduce preference. The colors red, green, and orange most strongly influenced participants' assessments, indicating that gamut shape, in addition to gamut area, is an important component of predicting color preference.